Analyzing the Impact of Government Policy on Poverty Alleviation: Evaluating Social Protection Programs, Healthcare Access, and Economic Reforms - Saputra, Gruskin Rosato (IHSA Institute, 2024)
This research investigates the impact of government policy on poverty alleviation, focusing on the effectiveness of various policy interventions and their influence on reducing poverty levels. Using a mixed-methods approach, the study combines quantitative analysis of statistical data with qualitative insights from surveys, interviews, and case studies. The research explores key areas including social protection programs, healthcare and education policies, economic reforms, and efforts to address systemic inequalities. Findings reveal that social protection programs, particularly conditional and unconditional cash transfers, are highly effective in providing immediate financial relief and fostering long-term human capital development. Healthcare policies that ensure access to affordable services significantly reduce the financial burden on poor households, preventing health-related poverty exacerbation. Education policies contribute to long-term poverty reduction by improving educational attainment and economic opportunities. Economic policies promoting job creation and inclusive growth, including fiscal measures and targeted economic reforms, enhance economic participation and empower marginalized communities.